HISTORY OF LANDSCAPE TERMS AND IT’S USAGE (American Journal of Interdisciplinary Research and Development, 2023)
In 1975, D.L. Armand emphasized that it is a necessary condition for "creating a clear scientific theory" - a set of "clear definitions" of concepts (definitions) used in science" , the task for which is to "regulate the conceptual and terminological apparatus of landscape science" went and presented the result of this work in the form. In the early 1980s, the "explanatory dictionary" in front of landscape scientists was established by the 20th century A.G. Isachenko (1982) [48, p. 15]. Unfortunately, it must be recognized that today There is no such terminological landscape dictionary. Some of these terms are included in general geographical or physiographic dictionaries and encyclopedias, as well as in various scientific publications (monographs, textbooks, educational benefits, etc.) in the main part or in appendices. However, , it should be noted that the definitions, which authors often offer for the same conditions, differ in content. The same situation makes it difficult not only for students to study landscape science, but also creates certain difficulties in the work of specialists. The textbook is represented by a dictionary, that is, an integral part of the educational and methodological complex and contains the conceptual and terminological minimum, knowledge necessary when studying the science of "Landscape Studies". The terminological field of the dictionary is divided into thematic sections. In some cases, for example, when considering existing classifications of landscapes, subsections are highlighted. The order of terms within sections and sections follows a hierarchical structure (for example, for a smaller unit rather than a larger alphabetical order). Two-word and multi-word terms are partially given by linguistic inversion, when the main semantic noun (for example, "alpine landscapes", not "alpine landscapes"). The definition of the term can be presented in different forms.